SUSTAINABLE DEVELOPMENT CONCEPTS INCLUDED IN HISTORY TEXTBOOKS FOR THE PREPARATORY STAGE IN THE REPUBLIC OF IRAQ AND THEIR COUNTERPARTS IN THE SYRIAN ARAB REPUBLIC A COMPARATIVE CONTENT ANALYSIS STUDY (American Journal of Research in Humanities and Social Sciences, 2026)
This study aimed to identify the extent to which sustainable development concepts are incorporated into history textbooks for the preparatory stage (literary branch) in the Republic of Iraq and their counterparts in the Syrian Arab Republic. To achieve this objective, the researchers employed the descriptive approach using content analysis methodology. A research instrument was developed consisting of 27 sub-items distributed across three main dimensions: the social dimension (10 items), the economic dimension (9 items), and the environmental dimension (8 items). The validity and clarity of the instrument were verified by presenting it to a panel of experts specializing in teaching methods, measurement and evaluation, educational psychology, and sustainable development. An agreement rate of 80% or higher was considered acceptable. To establish reliability, two procedures were adopted: reanalysis by the researchers after a time interval, and analysis conducted by external coders. The resulting agreement coefficients were high and sufficient for the purposes of the study. Data were statistically analyzed using frequencies, percentages, Holsti’s formula, and arithmetic means. The findings indicated that history textbooks for the secondary stage in the Syrian Arab Republic surpassed their Iraqi counterparts in terms of the overall frequency of sustainable development concepts across the social, economic, and environmental dimensions. The total number of occurrences in Syrian history textbooks reached 940, compared to 762 occurrences in Iraqi preparatory-stage history textbooks. In light of these findings, the researchers proposed several recommendations and suggestions.